TECHNOLOGY OF TEACHING TECHNOLOGIES OF THE VOLLEYBALL GAME TO PRIMARY SCHOOL STUDENTS AT THE TRAINING LEVEL (Academia Science Repository, 2023)
Teaching volleyball to primary school students at the training level can be a challenging task, but with the help of technology, it can become easier and more effective. In this article, we explore the various technologies that can be used to teach volleyball to young children and discuss best practices for doing so. We also present case studies of successful implementations of technology in teaching volleyball to primary school students. The article highlights the benefits of using technology in teaching volleyball, such as increased engagement, interactivity, and accessibility. Furthermore, it identifies areas for further research and development, such as the use of artificial intelligence, machine learning, and robotics. By incorporating technology into sports education, we can promote physical activity, teamwork, and coordination among young students, which can have a positive impact on their overall health and well-being.